Reforms of Political Finance: Strengthening Democracy by Reducing the Impact of High-Cost Politics - Dirkareshza, Rianda; Simanjuntak, Anni Alvionita; Zaifa, Gilang Abi (Ministry of Home Affairs, 2024)
This study has two objectives: First, to examine high-cost politics in Indonesian elections; Second, to propose measures to strengthen the Ministry of Home Affairs’ authority in political finance supervision and enhance regulations to promote electoral transparency, using the recent Indonesian elections as a case study. Indonesia’s political process is characterized by high-cost politics, where candidates often face pressure to raise substantial funds to finance their election campaigns. Consequently, elections, meant to serve as a democratic platform for all Indonesians, frequently become subject to abuse by individuals seeking to attain power. The primary goal of this study is to gain a comprehensive understanding of the high-cost politics in Indonesian elections and its impacts on democratic integrity. The study utilized a normative juridical methodology, incorporating statutory and conceptual approaches. The findings indicated that transactional and money politics, along with high-cost politics in Indonesia’s elections, pose a serious threat to democracy. The Ministry of Home Affairs and the General Election Supervisory Agency must strengthen their legal instruments to monitor political party finances. Furthermore, political actors must be encouraged to reduce high-cost politics.